(untitled) (Acta Theologica, 2017)
Preaching can rightly be called “foolishness”, an outdated form of communication and a feeble form of art. In democratic South Africa, preaching is certainly not assigned a place among the ranks of professions conveying “development”. Allan Boesak, however, has not been swayed by the excommunication of preaching since the dawn of democracy. In this article, I will contemplate Boesak’s fascination with preaching “Truth to power”. Boesak, as a son of liberation and Black theology, is known for aspiring to a new world through the biblical witness. In essence, preaching the biblical truths to power. Therefore, when academics contemplate the state of preaching and express concern with regards to how power operates in our society and faith communities, Boesak certainly has a contribution to make. I briefly examine how power operates in the South African society. Boesak’s publications and sermons are contemplated in the hope of uncovering his fascination with preaching truth to power. I conclude with some thoughts on how Boesak preaches truth to power for both the dismal state of preaching and how power operates in South Africa.